Untargeted lipidomic analysis of milled rice under different alternate wetting and soil drying irrigation regimes - Yunji Xu; Xuelian Weng; Shupeng Tang; Weiyang Zhang; Kuanyu Zhu; Guanglong Zhu; Hao Zhang; Zhiqin Wang; Jianchang Yang (Journal of Integrative Agriculture)
Alternate wetting and soil drying irrigation (AWD) technique is crucial in influencing grain quality in rice (Oryza sativa L.). Lipids are the third most abundant constituents in rice grains, after starch and proteins, and are closely related to grain quality. However, it remains unclear about the changes in lipids profiling under different AWD regimes. This study set up three irrigation regimes including conventional irrigation (CI), alternate wetting and moderate soil drying irrigation (AWMD), and alternate wetting and severe soil drying irrigation (AWSD). It explored lipidome changes in milled rice of Yangdao 6 (YD6) using the untargeted lipidomics approach and analyzed rice cooking and eating quality. The results identified seven lipid classes, 55 lipid subclasses, and 1,086 lipid molecular species. Compared with the CI regime, the AWMD regime mainly altered lipid subclasses consisting of triglyceride (TG), ceramide (Cer), diglyceride (DG), bis-methyl lysophosphatidic acid (BisMePA), phosphocholine (PC), phosphoethanolamine (PE), monogalactosyldiacylglycerol (MGDG), and digalactosyl diglyceride (DGDG) in milled rice and improved cooking and eating quality of rice; in contrast, the AWSD regime distinctly changed lipid subclasses like TG, Cer, DG, PC, PE, hexosylceramide (Hex1Cer), DGDG, and BisMePA and degraded cooking and eating quality of rice. Specifically, AWMD most significantly altered the expressions of lipid molecules, including DGDG(18:0_18:2), DGDG(16:0_14:0), PC(33:1), Cer(t17:0_26:0), and Cer(t17:0_16:0); AWSD most obviously influenced the expressions of TG(6:0_14:0_18:3), PC(41:1), TG(19:1_18:4_18:4), Hex1Cer(d18:2_24:0+O), and Hex1Cer(d18:2_24:1). These 10 altered lipid molecules in milled rice can be preferentially used for investigating their relationships with grain quality in rice.